An important personality of psychosurgery: the italian psychiatrist Mario Adamo Fiamberti (1894-1970) - Aliverti, Massimo (Medicina Historica, 2019)
This letter is about the life and the research of an Italian psychiatrist, who had national and international reputation in the 20th century, especially for his interest in “psychosurgery”.